The clinical features and real world treatment outcomes in von Hippel Lindau related retinal capillary hemangioblastomas - Abdulrahman Khan; Wael A. Alsakran; Abdullah Barry; Abdulrahman H. Badawi; Moustafa S. Magliyah (International Journal of Retina and Vitreous)
Abstract Background and objective To present the clinical features and outcomes of treatment in von Hippel-Lindau (VHL) related retinal capillary hemangioblastoma (RCH). Methods A retrospective interventional cohort study that included Patients who were diagnosed with VHL-related RCH from 2014 to 2024 at a tertiary referral center. Results Thirty-two eyes of 18 patients with VHL-associated RCH were included. Treatment was indicated in 30 eyes (90.9%), and the indications for treatment were tumor leakage and subretinal fluids (SRF) with or without exudative retinal detachments in 25 eyes (83.3%) and tractional/exudative retinal detachments (T-ERD) in 4 eyes (13.3%). Significantly worse visual outcomes were observed in patients who had lower BCVA on presentation, larger tumor sizes, developed retinal complications, underwent retinal surgery, detached retina on the last follow up and had persistent tumor outcomes. Conclusion The management outcomes in VHL-related RCH depend on the lesionsize and location, severity of the clinical picture on presentation and the development of complications. Clinical trial number Not applicable.